Menopause and cardiovascular disease. Issue 1 (March 2018) - Newson, Louise
Cardiovascular disease is very common in women. It is still under diagnosed and under treated. Many women are not having their risk factors for cardiovascular disease properly addressed. Many healthcare professionals are uncertain about the role of hormones in cardiovascular disease. This article gives an overview of the most important risk factors for cardiovascular disease and how to manage those risk factors appropriately, based on the available evidence.